Effective treatment of benign biliary strictures with a removable, fully covered, self-expandable metal stent: A prospective, multicenter European study. Issue 3 (April 2017) - Schmidt, Arthur; Pickartz, Tilman; Lerch, Markus M; Fanelli, Fabrizio; Fiocca, Fausto; Lucatelli, Pierleone; Cereatti, Fabrizio; Hoffmeister, Albrecht; van Steenbergen, Werner; Kraft, Matthias; Meier, Benjamin; Caca, Karel
Background: Temporary placement of removable, fully covered, self-expandable metal stents (fcSEMS) for treatment of benign biliary strictures (BBS) has been reported to be effective. However, the optimal extraction time point remains unclear and stent migration has been a major concern. Objective: The objective of this study was to evaluate the efficacy and safety of this treatment modality using an fcSEMS with a special antimigration design and prolonged stent indwell time. Methods: We performed a prospective, single-arm study at six tertiary care centers in Europe. Patients with BBS underwent endoscopic or percutaneous implantation of an fcSEMS (GORE® VIABIL® Biliary Endoprosthesis, W.L. Gore & Associates, Flagstaff, AZ, USA). The devices were scheduled to be removed nine months later, and patients were to return for follow-up for an additional 15 months. Results: Forty-three patients were enrolled in the study. Stricture etiology was chronic pancreatitis in the majority of patients (57.5%). All fcSEMS were placed successfully, either endoscopically (76.7%) or percutaneously (23.3%). Stent migration was observed in two patients (5.2%). Primary patency of the SEMS prior to removal was 73.0%. All attempted stent removals were successful. At removal, stricture was resolved or significantly improved without need for further therapy in 78.9% of patients. Stricture recurrence during a follow-up of two years post-implant was observed in two patients. Conclusions: Temporary placement of the fcSEMS is a feasible, safe and effective treatment for BBS. The design of the device used in this study accounts for very low migration rates and facilitates easy stent retrieval, even after it has been in place for up to 11 months.